Interleukin-1 two-locus haplotype is strongly associated with severe chronic periodontitis among Yemenis - Al-Hebshi, Nezar Noor; Shamsan, Amat-Alrahman Ahmed; Al-Ak'hali, Mohammed Sultan (Wiley, 2012)
Aim. To assess IL-1A C[?889]T and IL-1B C[3954]T genotypes as well as haplotypes in relation to sever chronic periodontitis (SCP) among Yemenis. Materials and Methods. 40 cases with SCP and 40 sex- and age-matched controls were included; all were nonsmokers and free of systemic diseases. Genotyping at each locus was performed using an established PCR-RFLP assay. The Haploview and SimHap software were used to assess data for Hardy-Weinberg?s equilibrium (HWE) and linkage disequilibrium (LD) and to obtain subject-level haplotypes. Multiple logistic regression was used to seek for associations in dominant, additive, and recessive models. Results. Mean plaque index (MPI) showed the strongest association with SCP (OR = 16). A significant LD was observed in the cases (D? = 0.80 and r2 = 0.47). The genotype at each locus showed significant association with SCP in the recessive model (TT versus TC + CC) even after adjustment for MPI (OR = 6.29 & 461, resp.). The C-T haplotype conferred protection against SCP in a dominant manner (OR = 0.16). On the other hand, the T-T haplotype in double dose (recessive model) showed strong association with CP (OR = 15.6). Conclusions. IL-1 two-locus haplotype is associated with SCP in Yemenis. Haplotype-based analysis may be more suited for use in genetic association studies of periodontitis.